Pityous and its mosaics - Plontke -Luening, A. (Херсонесский сборник, 2006)
“Setting out from Dioskourias the first harbour will be in Pityous, at a distance of 350 stadia” reports Flavius Arrianus in his Periplous Ponti Euxini (peripl. 18, 1). The governor of Cappadocia and his representative fleet – one trireme and some liburnae – traveled in 134 AD along the Eastern Pontos shore and inspected the Roman garrisons between Trapezous and the “end of the Roman dominion” which was at his time in Dioskourias-Sebastopolis. Continuing the journey to the Crimea Arrian came to Pityous which was the first harbour after Sebastopolis, at a distance of 350 stadia. So there was no Roman garrison at Pitiunt in Hadrianic time. But it seems that the journey of Arrian gave the impetus to install in Pityous Roman forces because he recognized the importance of the place for the grain transport from the Northern Pontos to Trapezous which was the supply base for the Roman forces in Anatolia.